Comunidades de prática no espaço escolar: possibilidades para o exercício e qualificação docente - Lopes, Andressa Freitas (2022)
Among the characteristics which define educational environments – from the professional formations to the teaching on the Basic Education – is the predisposition to collective work. In this bias, are studied Communities of Practice (CoP), which are defined as a group of individuals who interacts according to a theme/interest, participating of collaboration processes, through shared knowledge, resources and practices, to construct both personal and collective knowledge. Under this perspective, we aim to analyze possible spaces/moments occupied by teachers who actuate on the Basic Education that may constitute a Community of Practice relevant to teaching practice and qualification. To achieve it, we have the following specific objectives: (a) map the potential school`s spaces and moments which are close and/or far from the formation and maintenance of a Community of Practice; (b) investigate these spaces contributions` to the teachers` qualification and; (c) describe the process of self-formation, as a researcher, inside a CoP. This research effort, of a qualitative-quantitative imprint, consists of generating data by means of survey questionnaires and semi-structured interviews with teachers who actively work on the Basic Education. To make these materials we adopted the three dimensions of practice – mutual engagement, joint undertaking and shared repertoire – and the senses of identity and belonging. Starting from the generated data, we employed the content analysis to investigate and process data. We inferred that all school spaces studied here have potential to be a Community of Practice, some with bigger nuisances, other quite close of being a CoP themselves. Amongst the furthest from the formative axis of a CoP, we find the “collegiates and commissions” and “parents and teachers’ meetings”. As the constituents of a CoP, presenting and reaffirming all the necessary formative axis, we obtained “pedagogical formations” and “pedagogical meetings”. As we pored over the second one, which had the highest positive frequency related to the CoP axis, we confirmed with the teachers its constitution, presenting the three dimensions of practice and strongly evidenced identity and belonging` senses. As a result of this, the “pedagogical meetings” have proven themselves to be relevant to the teachers` qualification, being capable of promoting their identity and belonging senses towards their school and community, study other areas, optimize their time of study and planning, acquiring new knowledge, among others. It is also asserted by this dissertation`s author, on an auto-bibliographical exercise, that being in a CoP has allowed working in a collective and collaborative manner, has motivated her to be and stay in graduate school, has favored spontaneous and clear learning about the Science Education area. Therefore, schools and universities that enjoy the use of a CoP to form groups, concede to teachers and students countless moments of qualification which assists the enhancement of teacher` praxis, conviviality with the collective and growth as a human being, as well as motivate them to recognize themselves as active participants of a society and of a democratic education.